The Effect of Audio Visual Learning Media and Learning Motivation on Science Learning Outcomes of Grade VII Students - Ayu Permata Sari; Alhadi Yan Putra; Muhammad Fahmi (PPSDP International Journal of Education, 2026)
This study determined and described the effect of audiovisual learning media and learning motivation on the science learning outcomes of Grade VII students at public junior high schools (SMP) in Sako District, Palembang. The research sample consisted of 61 Grade VII students from two schools: SMP Mandiri Palembang (29 students) and SMP Binatama Palembang (32 students). Sampling techniques included total sampling and cluster random sampling. Data were collected by distributing questionnaires featuring a 5-point Likert scale to measure 60 statement items, alongside a final assignment comprising 30 questions. The data analysis technique employed was simple and multiple linear regression analysis. The results indicated that: 1) There is a significant influence of audiovisual learning media on the science learning outcomes of Grade VII students. 2) There is a significant influence of learning motivation on the science learning outcomes of Grade VII students. 3) Collectively, audiovisual learning media and learning motivation significantly influence the science learning outcomes of Grade VII students at the studied schools in Sako District, Palembang. The findings suggest that educators and institutions should consider integrating audiovisual media into their teaching strategies and actively work to enhance student learning motivation to improve science learning outcomes in junior high school settings. This study contributes to the existing literature by simultaneously examining the combined and individual effects of audiovisual learning media and learning motivation on science learning outcomes within a specific Indonesian educational context. It provides empirical evidence supporting the importance of both technological tools and psychological factors in achieving better academic performance.